Особливості нелінійного наративу при побудові інтерактивного сторітеллінгу - Джиджора, Євген; Мельник, Сергій; Трояновська, Юлія (Видавництво Львівської політехніки, 2019)
Computer games as a modern form of interpersonal communication. In computer games, interactive storytelling suggests a non-linear presentation, based on the category of choice. The player as an active storyteller and game script organizer. The game «The Adventures of Baron Munchausen» was developed on the principle of nonlinear presentation.
Keywords: cторітеллінг; наратив; комунікація; комп’ютерна гра; інтерактивне кіно; геймдизайн